Recent advances in the development of smart, active, and bioactive biodegradable biopolymer-based films containing betalains - Oliveira Filho, Josemar Gonçalves de [UNESP]; Bertolo, Mirella Romanelli Vicente; Rodrigues, Murilo Álison Vigilato; Silva, Guilherme da Cruz; Mendonça, Giovana Maria Navarro de [UNESP]; Bogusz Junior, Stanislau; Ferreira, Marcos David; Egea, Mariana Buranelo (Elsevier, 2022)
Betalains are natural nitrogenous water-soluble pigments found in species belonging to the Caryophyllales order and in mushrooms. Betalains can be considered multifunctional molecules due to their diverse bioactivities such as antioxidant, antimicrobial, anticancer, and anti-inflammatory. Furthermore, they can detect pH variations in foods and are considered promising colorimetric bioindicators. The bioactivities of betalains have improved their use as active and bioactive agents, and colorimetric indicators in the development of edible and biodegradable films for foods, which are trends in the food packaging market. Thus, this review presents the state-of-art information on the use of betalains as a multifunctional molecule in the development of smart, active, and bioactive edible and biodegradable packaging for foods. Studies have revealed that betalains can be successfully used to develop: smart films to indicate the freshness and spoilage of foods such as shrimp, fish, and chicken; active films with antimicrobial and antioxidant potentials to increase the shelf life of sausage and shrimp; and bioactive films with health benefits.
Keywords: active packaging; betalains; natural pigment; pH indicator; smart packaging